Zero-based budget performance analysis as a budgeting tool in a mixed economy company - Lima, Maria Luiza; Cunha, Edileuza Lobato da; Lima, Orlem Pinheiro de; Araújo, Paulo César Diniz de; Maduro, Márcia Ribeiro; Júnior, Nilson José de Oliveira; Roberto, José Carlos Alves; Roberto, Ana Paula Alves (Seven Editora, 2023)
The article aims to analyze the performance of Zero-Based Budgeting (ZBB) as a budgeting tool in a mixed economy company, from 2018 to 2021. The research was conducted through a case study of qualitative approach where there were two analyses. The first was the data of realized, budgeted and the variation of expenses and investments of the organization, and the second is the analysis of the methodology through a questionnaire answered by the team responsible for Budget Control regarding the negative and positive aspects of the ZBB. It was observed that the registration of events organized in a Budget Plan will not necessarily cause them to be fully realized, and that the methodology stands out for the budget control resulting from its rich detailing. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-140